Fe doped NiSe2 nanoarrays to boost electrocatalytic oxygen evolution reaction. (1st September 2022) - Tian, Zhangmin; Liu, Yanxia; Xu, Qiuchen; Shi, Yingying; Ma, Chenxu; Peng, Bin; Liu, Guiying; Yang, Jianing; Zheng, Wenjun
Highlights: Fe doped NiSe2 on carbon cloth (CC) catalysts were synthesized by a two-step hydrothermal method. Ni0.8 Fe0.2 Se2 /CC is evidenced by the overpotential of 257 mV at the current density of 10 mA cm −2, and Tafel slope of 43 mV dec −1 . Doping engineering strategy makes Ni0.8 Fe0.2 Se2 /CC manifest a superb performance for OER. Ni0.8 Fe0.2 Se2 transforms into NiFe-based (oxy)hydroxides, which serves as "real" active phase. Abstract: Transition metal selenides (TMSes) have attracted increasing attention for electrocatalysts due to fascinating properties, such as low cost, intrinsic metallic properties, and high catalytic activities. In addition, bimetallic selenides exhibit more excellent performance in the oxygen evolution reaction (OER) process than monometallic selenides via synergistic effect. Herein, we synthesized Fe doped NiSe2 on carbon cloth (CC) employed as electrodes for boosting OER by a facile two-step hydrothermal method. These electrodes display excellent electrocatalytic activity for OER in alkaline electrolytes, in which Ni0.8 Fe0.2 Se2 /CC is evidenced by the overpotential of 257 mV at the current density of 10 mA cm −2, and Tafel slope of 43 mV dec −1 . The synthesized three-dimensional structure with the aid of carbon cloth helps for the mass and charge transfer. Furthermore, Fe doping not only induces stronger electron interaction but tunes electronic structure, thus improving the OER performance. After a long-term OER process, Ni0.8 Fe0.2 Se2 transforms into NiFe-based (oxy)hydroxides, which may serve as "real" active phase. Doping engineering strategy makes TMSes manifest a superb performance for OER and expands ways for designing effective OER electrodes. Graphical abstract: Herein, we synthesized Fe doped NiSe2 on carbon cloth (CC) employed as electrodes for boosting OER by a facile two-step hydrothermal method. These electrodes display excellent electrocatalytic activity for OER in alkaline electrolytes, in which Ni0.8 Fe0.2 Se2 /CC is evidenced by the overpotential of 257 mV at the current density of 10 mA cm −2, and Tafel slope of 43 mV dec −1 . Fe doping not only induces stronger electron interaction but enlarges Ni 3+ /Ni 2+ ratio, thus improving the OER performance. Ni0.8 Fe0.2 Se2 transforms into NiFe-based (oxy)hydroxides, which serve as "real" active phase in OER process. Image, graphical abstract